2012
DOI: 10.1007/s13758-012-0031-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Protein Adsorption on Atmospheric Plasma Deposited Coatings Exhibiting Superhydrophilic to Superhydrophobic Properties

Abstract: Protein adsorption is one of the key parameters influencing the biocompatibility of medical device materials. This study investigates serum protein adsorption and bacterial attachment on polymer coatings deposited using an atmospheric pressure plasma jet system. The adsorption of bovine serum albumin and bovine fibrinogen (Fg) onto siloxane and fluorinated siloxane elastomeric coatings that exhibit water contact angles (θ) ranging from superhydrophilic (θ < 5°) to superhydrophobic (θ > 150°) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
92
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(96 citation statements)
references
References 43 publications
1
92
2
1
Order By: Relevance
“…7 However, in recent years, silica, 8 silicon 9 and silicon-coated materials, 10 have been proposed as in vivo bio-materials. When these materials are introduced into the body, the external part interacts with water, and a specific aqueous interface is created.…”
Section: Introductionmentioning
confidence: 99%
“…7 However, in recent years, silica, 8 silicon 9 and silicon-coated materials, 10 have been proposed as in vivo bio-materials. When these materials are introduced into the body, the external part interacts with water, and a specific aqueous interface is created.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also shown that the production of the local factor, osteoprotegerin (which serves as a decoy receptor for RANKL to inhibit osteoclastogenesis and to favor net bone formation 21 ), is strongly influenced by the hierarchically microroughened surfaces, 41 and it is believed that integrins such as α2β1, 42,43 among the favored protein aggregations on surface topography, are crucial to enhance cell osteogenesis on group 2 surfaces. In addition, hydrophilic material surfaces are better for cell attachment, spreading, and cytoskeletal organization; however, superhydrophilic surfaces, like those of group 3, are not beneficial for protein adsorption, 44,45 resulting in poor cell functions. On the other hand, the appropriate Ca ion levels have been shown to stimulate osteoblast proliferation and differentiation by changing the expression of specific Ca 2+ channel isoforms on osteoblasts.…”
mentioning
confidence: 99%
“…Similar to protein adhesion, hydrophobic surfaces are less resistant to bacterial adhesion [21]. However, super hydrophobic surfaces containing siloxane and fluorosiloxane have been shown to reduce protein adsorption and bacterial adhesion [33]. However, PTFE surfaces and resin composites with PTFE particle additives have been unable to inhibit protein adsorption and bacterial adhesion [20,21].…”
Section: Discussionmentioning
confidence: 99%